HUBUNGAN PERAN PERAWAT DALAM PEMBERIAN TERAPI SPIRITUAL TERHADAP PERILAKU PASIEN DALAM PEMENUHAN KEBUTUHAN SPIRITUAL DI RUANG ICU RSM AHMAD DAHLAN KOTA KEDIRI - Yaseda, Grace Yopi; Noorlayla, Siti Farida; Efendy, Muhamad As'ad (STRADA : Jurnal Ilmiah Kesehatan, 2013)
A patient in addition to requiring medical treatment also need spiritual assistance to deal with the disease and support the recovery. For that nurses should be able to perform its role in creating comfort through spiritual therapy. The purpose of this study was to determine the relationship of the nurse’s role in spiritual therapy to the patient’s behavior in meeting the spiritual needs at ICU Room Muhammadiyah Hospital Ahmad Dahlan Kediri. Study design was cross-sectional correlational approach. The population was all patients in ICU Room RSM Ahmad Dahlan Kediri with a sample of 20 respondents taken by purposive sampling technique. The independent variable role of nurses in providing spiritual and dependent behavior therapy in patients spiritual needs were collected by questionnaire. Data are expressed in an ordinal scale and were analyzed by Spearman rho correlation test with error level (α) = 0.05. Of the 20 respondents largely assess the role of nurses in providing spiritual therapy including both category ie 15 respondents (75%), behavior in meeting the spiritual needs include both categories, namely 14 (70%) and no relationship nurse’s role in spiritual therapy with the patient ‘s behavior the spiritual needs (Spearman’s Rho with p = 0.003 < 0.05 then Ho is rejected). Rate and direction of relationships including moderate positive relationship, meaning that the better behavior of nurses in the delivery of spiritual therapy, the better the patient ‘s behavior in the spiritual fulfillment and vice versa (correlation coefficient 0.630). Spiritual therapy by a nurse to the patient can change and improve behavior in spiritual fulfillment. It is suggested that the role of nurses still run as good as possible to every patient.